Factors associated with people's behavior in social isolation during the COVID-19 pandemic - Bezerra, Anselmo César Vasconcelos; Silva, Carlos Eduardo Menezes da; Soares, Fernando Ramalho Gameleira; Silva, José Alexandre Menezes da (Ciência & saude coletiva, 2020)
This paper presents the results of an opinion poll conducted in Brazil on the perception of social isolation during the COVID-19 pandemic. The questionnaire was prepared on Google Forms, disseminated through social networks, with questions about the socioeconomic profile and factors associated with isolation. A non-probabilistic sample was obtained with 16,440 respondents. Data were analyzed using the Stata 13 software. Social interaction was the most affected aspect among people with higher education and income (45.8%), and financial problems caused a more significant impact (35%) among people with low income and education. Those who practice some physical activity showed lower levels of stress 13%, as well as greater normality in sleep 50.3%. People who reported living in worse habitability conditions reported willingness to remain isolated for less time, 73.9%. Among non-isolated people (10.7% of the total sample), 75.8% believe that social isolation will reduce the number of victims of COVID-19. We conclude, based on this sample, that the perception about social isolation as a pandemic mitigation action varies by income, education, age, and gender. However, most believe that it is the most appropriate control measure and are willing to wait as long as necessary to contribute to the fight against COVID-19.